Analysis of electromagnetic torque for induction motors with a novel non-skewed rotor structure. Issue 1 (19th November 2021) - Darjazini, Amir; Vahedi, Abolfazl; Nobahari, Amin; Gharehseyed, Saber
Abstract : Purpose: Pulsating torques cause a number of problems in electrical machines, including mechanical vibrations, acoustic noise and the depreciation of mechanical equipment. In induction motors, the slot skewing method is an effective way to solve these issues; however, it has some drawbacks such as output torque drop, stray loss intensification due to inter-bar currents and iron loss increment. Besides, slot skewing may not be practical in higher-rated induction motors. In this regard, this paper introduces a modified non-skewed rotor (MNSR) structure as a possible alternative to the skewed designs. Design/methodology/approach: The proposed structure includes a two-segmented rotor with an intermediate ring between the rotor parts that are mounted on the shaft with a relative shift angle. Detailed information about the idea and structure of the MNSR as well as its manufacturing aspects will be presented in the second section of the paper. First, the working principle of the proposed design is described via analytical equations to provide an insight into the concept. The shifting angle will then be calculated by analyzing the harmonic contents of the electromagnetic torque. Finally, the validity of the analytical method will be verified by developing three-dimensional finite element models. Findings: It is demonstrated that by using the proposed rotor structure, the torque ripple has been reduced to a satisfactory level without significantly affecting the mean torque, unlike the skewing method. Furthermore, the new method could avoid the disadvantages of the skewing method while enhancing other motor characteristics such as iron loss. Also, the total volume of the MNSR is equal to the initial design, and the mass and material differences are also negligible. Originality/value: In this paper, a MNSR is introduced as a possible alternative to the skewed patterns. The study mainly focused on electromagnetic torque profile characteristics, i.e. the mean torque enhancement and the ripple reduction. The MNSR structure can be used for general purposes and high-performance applications, especially where excellent torque characteristics are required.